Measurement of the combined rapidity and p(T) dependence of dijet azimuthal decorrelations in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M. (2013)
We present the first combined measurement of the rapidity and transverse momentum dependence of dijet azimuthal decorrelations, using the recently proposed quantity R-Delta phi. The variable R-Delta phi measures the fraction of the inclusive dijet events in which the azimuthal separation of the two jets with the highest transverse momenta is less than a specified value of the parameter Delta phi(max). The quantity R-Delta phi is measured in p (p) over bar collisions at root s = 1.96 TeV, as a function of the dijet rapidity interval, the total scalar transverse momentum, and Delta phi(max). The measurement uses an event sample corresponding to an integrated luminosity of 0.7 fb(-1) collected with the DO detector at the Fermilab Tevatron Collider. The results are compared to predictions of a perturbative QCD calculation at next-to-leading order in the strong coupling with corrections for non-perturbative effects. The theory predictions describe the data well, except in the kinematic region of large dijet rapidity intervals and small Delta phi(max). (C) 2013 Elsevier B.V. All rights reserved.